Avian Influenza Virus H5N1 Remained Exist in Gastrointestinal Tracts of House Flies 24 Hours Post-infection) (VIRUS FLU BURUNG H5N1 TETAP BERADA DALAM SALURAN PENCERNAAN LALAT RUMAH 24 JAM PASCAINFEKSI) - Tyasasmaya, Tisna; Wuryastuty, Hastari; Wasito, Wasito; Sievert, Kai (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
House flies (Musca domestica L.) are one of the major pests found in poultry farms resulting in not onlyannoyance and indirect damage to the poultry production but also transmitting many infectious organismsmechanically and biologically. A highly pathogenic avian influenza virus H5N1 (HPAIV H5N1) collectedfrom field house flies in Java Island, have fully succeeded identified and isolated in 2008. The AIV H5N1isolates were further used in the present study to determine the presence and persistence of the AIV H5N1in the laboratory infected house flies. One hundred house flies from a free AIV poultry farm in Yogyakarta,Indonesia were used in this study. The collected house flies were fasted for 12 hours then divided equallyin control and treated groups. The treated group was allowed to imbibe Dulbecco’s modified eagle medium(DMEM) containing AIV H5N1 while the control group imbibed medium without virus for one hour. Theflies from each group were collected at 12 and 24 hours post-exposure, respectively. All flies were immobilizedat 4°C, immersed in absolute ethanol for a few seconds and dissected under the stereomicroscope to collectthe gastrointestinal (GI) tracts. Based on the RT-PCR results, it is concluded that AIV H5N1 remainedexist in GI tracts of house flies for at least 24 hours post-exposure.
Keywords: house flies (Musca domestica L.); mechanical and biological vectors; avian influenza virus H5N1; gastrointestinal tracts; RT-PCR